PENGARUH NILAI TUKAR DAN SUKU BUNGA TERHADAP INVESTASI DI PROVINSI ACEH - Maria Ulfah, Mohd Nur Syechalad, Abubakar Hamzah. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2014)
Abstract : Investment is an important factor in a country or region in order to improve its economy. Investment will increase public spending which will result in far-reaching effects. Investment in Aceh province is the lowest level in Indonesia. Not only in small quantities, but also fluctuated over years. Especially, when it is compared to the national investment from 1984 to 2010. The average of Aceh investment province is only 2 % of the total Aceh GRDP. This study attempts to show the relationship and the effect of exchange rates and interest rates on investment in Aceh Province also the influence of the previous year's investment in current investments. Investigating the relationship and influence between the variables, the Ordinary Least Square (OLS) and autoregressive methods is used in this study. The study has shown that the exchange rates has a little effect on investment in Aceh Province, while interest rate has no effect on investment in Aceh Province. This situation occurs (especially in Aceh province) because of the ongoing conflict. It is expected that the study will be followed by a more focused research again to overcome the limitations of this study. Keyword : Investment, Exchange Rate, Interest Rate. Abstrak : Investasi adalah hal yang penting dalam rangka membangkitkan perekonomian disuatu negara atau wilayah . Investasi akan meningkatkan pengeluaran masyarakat yang akan menghasilkan efek yang luas . Investasi di provinsi Aceh berada di tingkat terendah . Tidak hanya dalam jumlah kecil , tetapi juga berfluktuasi selama bertahun-tahun. Apalagi jika dibandingkan dengan investasi nasional dari tahun 1984 sampai 2010 , investasi rata-rata provinsi Aceh hanya 2 % dari jumlah PDRB Aceh . Studi ini mencoba untuk menunjukkan hubungan dan pengaruh nilai tukar dan suku bunga terhadap investasi di Provinsi Aceh . Juga pengaruh investasi tahun sebelumnya pada investasi saat ini. Untuk menunjukkan hubungan dan pengaruh antara variabel , penelitian ini menggunakan Ordinary Least Square (OLS) dan Metode Autoregressive. Penelitian ini telah membuktikan bahwa nilai tukar dan suku bunga memiliki efek yang kecil atau korelasi antara variabel tidak signifikan di Provinsi Aceh . Situasi ini terjadi ( terutama di Provinsi Aceh ) karena adanya konflik yang berkelanjutan . Diharapkan penelitian ini akan diikuti dengan penelitian yang lebih terarah lagi untuk mengatasi keterbatasan penelitian ini. Kata kunci : Investasi, Nilai Tukar, Suku Bunga.